Intraoperative Treatment of Duct of Luschka during Laparoscopic Cholecystectomy: A Case Report and Revision of Literature - Luigi Masoni; Leandro Landi; Riccardo Maglio (Case Reports in Surgery)
Background. Bile leakage still remains a serious complication during cholecystectomies. In limited cases, this complication may occur from injury of the so-called ducts of Luschka. These rare ducts are usually discovered intraoperatively, and their presence poses the risk of bile injury and clinically significant bile leak. Presentation Case. We present a unique case of a 59-year-old male patient with acute cholecystitis. After removal of the gallbladder, thorough inspection of the hepatic bed was made and a little bile leak was identified from a duct of Luschka 1 cm away from the gallbladder hilum. We report on the use of endoscopic QuickClip Pro® clips (Olympus Medical Systems Corp., Tokyo, Japan) to avoid further more invasive treatment. Discussion. Endoscopic retrograde cholangiopancreatography with sphincterotomy played a crucial role for diagnosis and treatment of bile leaks with success rate near 94%. Many authors have argued the role of relaparoscopy, Diagnosis may be intraoperatively but this option does not seem to occur very often; in fact, there is a lack of data in literature. Conclusion. This is the first case report of bile leak from duct of Luschka treated during the cholecystectomies with endoscopic clip.